HERBAL MEDICINES IN RESPIRATORY TREATMENT - Matushchak, M.; Zakharchuk , O.; Kostyshyn , L. (Collection of scientific papers «ΛΌГOΣ», 2024)
It is known that the use of medicinal plants, including as part of complex therapy, significantly expands therapeutic options and allows for better clinical results. WHO has called on governments of all countries to make traditional herbal medicine part of national health systems. The following requirements are imposed on drugs for the treatment of coughs that occur against the background of respiratory diseases: the drug should relieve inflammation of the respiratory tract, ensure their release due to secretolytic, secretomotor action and at the same time alleviate the cough itself, combat the cause of the disease and its complications, providing a comprehensive etiopathogenetic approach to treatment. These requirements are met by a drug that has a secretolytic, expectorant and anti-inflammatory effect due to the extracts of medicinal plants contained in its composition: thyme, ivy and primrose.